MENINGKATKAN NILAI PERUSAHAAN MELALUI STRATEGI INDUSTRI HIJAU, PROFITABILITAS, DAN CORPORATE SOCIAL RESPONSIBILITY: PERAN LEVERAGE SEBAGAI VARIABEL MEDIASI - Nadia, Ananta Arta; Indrati, Menik (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine the effect of green industry strategy, profitability, and corporate social responsibility on firm value with leverage as a mediating variable in companies listed in the LQ45 index during the 2021–2024 period. This research employs a quantitative approach using secondary data obtained from annual financial reports, sustainability reports, and PROPER rating data published by the Ministry of Environment and Forestry. The research sample was selected using purposive sampling, resulting in 20 companies with a total of 80 observations during the study period. Data analysis was conducted using panel data regression with the assistance of EViews 12 software. The selection of the best model was determined through the Chow test, Hausman test, and Lagrange Multiplier test to identify the most appropriate estimation model for each equation. The results indicate that green industry strategy and profitability have a negative and significant effect on leverage, while corporate social responsibility has no significant effect on leverage. In testing their impact on firm value, green industry strategy and profitability show no significant effect, corporate social responsibility has a negative and significant effect, and leverage has a positive and significant effect on firm value. The Sobel test results reveal that leverage mediates the relationship between green industry strategy and profitability and firm value, but does not mediate the relationship between corporate social responsibility and firm value. These findings suggest that investors respond more strongly to corporate financing structure decisions than to non-financial signals such as environmental strategies and social disclosures. Optimally managed leverage is perceived as a signal of financial strength that enhances market confidence and firm value, while CSR activities are still viewed as short-term costs that have not yet generated direct economic benefits.